2014
DOI: 10.5194/acp-14-6903-2014
|View full text |Cite
|
Sign up to set email alerts
|

Deriving an atmospheric budget of total organic bromine using airborne in situ measurements from the western Pacific area during SHIVA

Abstract: Abstract. During the recent SHIVA (Stratospheric Ozone: Halogen Impacts in a Varying Atmosphere) project an extensive data set of all halogen species relevant for the atmospheric budget of total organic bromine was collected in the western Pacific region using the Falcon aircraft operated by the German Aerospace agency DLR (Deutsches Zentrum für Luft-und Raumfahrt) covering a vertical range from the planetary boundary layer up to the ceiling altitude of the aircraft of 13 km. In total, more than 700 measuremen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(116 citation statements)
references
References 52 publications
10
102
1
Order By: Relevance
“…The model chemical fields are constrained by specified timedependent surface mixing ratios. For the brominated species, the following surface mixing ratios of stratosphericrelevant source gases are assumed: [CH 3 WMO, 2014;Sala et al, 2014). No other (unknown organic or inorganic) sources of bromine for UT, LS, and TTL are assumed (e.g., Salawitch et al, 2010;Wang et al, 2015).…”
Section: Photochemical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The model chemical fields are constrained by specified timedependent surface mixing ratios. For the brominated species, the following surface mixing ratios of stratosphericrelevant source gases are assumed: [CH 3 WMO, 2014;Sala et al, 2014). No other (unknown organic or inorganic) sources of bromine for UT, LS, and TTL are assumed (e.g., Salawitch et al, 2010;Wang et al, 2015).…”
Section: Photochemical Modelingmentioning
confidence: 99%
“…In the present context the most important were measurements performed within the TTL (for the definition of TTL, see Fueglistaler et al, 2009) over the Pacific from where most of the stratospheric air is predicted to originate (e.g., Fueglistaler et al, 2009;Aschmann et al, 2009;Hossaini et al, 2012b;Ashfold et al, 2012;WMO, 2014;Orbe et al, 2015). These include the measurements (a) by Schauffler et al (1993Schauffler et al ( , 1998Schauffler et al ( , 1999, who found [VSLS] = 1.3 ppt (contribution 3) at the tropical tropopause over the central Pacific (Hawaii) in 1996, (b) by Laube et al (2008) and Brinckmann et al (2012) Supporting information on brominated VSLS concentrations typical of the boundary layer of the western Pacific came from measurements performed during the TransBrom ship cruise in October 2009 (median 2.23 ppt and range from 1.45-4.14 ppt; Brinckmann et al, 2012) and the VSLS measurements made around Borneo during the SHIVA (Stratospheric Ozone: Halogen Impacts in a Varying Atmosphere) project (median 5.7 ppt and range from 3.9 to 10.7 ppt; Sala et al, 2014). Corroborating model calculations to these field studies by (a) Tegtmeier et al (2012) indicated that from the western Pacific on average only 0.4 ppt and at a maximum up to 2.3 ppt of the emitted VSLS bromine may reach the stratosphere, while (b) Liang et al (2014) estimated that up to 8 ppt of VSLS bromine may enter the base of the TTL at 150 hPa, whereby the VSLS emissions from the tropical Indian Ocean, the tropical western Pacific, and off the Pacific coast of Mexico are suspected to be most relevant, and finally (c) the Community Atmosphere Model with Chemistry (CAM-Chem) modeling performed within the study of Navarro et al (2015), which indicates that over the eastern and western Pacific contributions 3 and 4 (called [VSLS + Br inorg y ] in the study) amount to 6.20 ppt (range 3.79-8.61 ppt) and 5.81 ppt (range 5.14-6.48 ppt), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Where recent TTL data are available it is primarily from different regions and focussed on brominated VSLSs (e.g. Sala et al, 2014;Navarro et al, 2015).…”
mentioning
confidence: 99%
“…TOGA uses a custom-built liquid nitrogen (LN 2 ) fuelled system to cool sample enrichment traps down to −130 • C enabling a sample to be taken every 2-5 min. To our knowledge, three other fast GC systems have since been designed for aircraft operation: GhostMS (Sala et al, 2014), HCG (Jäger, 2014) and µDirac (Gostlow et al, 2010). None of the three require the use of a liquid cryogen and all have been successfully operated in aircraft, Zeppelin or balloon campaigns.…”
Section: E Bourtsoukidis Et Al: System For Organic Fast Identificatmentioning
confidence: 99%
“…Faster GC-MS cycling and therefore a higher number of chromatograms acquired creates the need for robust peak integration software. While most of the peaks could be analysed with IAU-Chrom software (Sala et al, 2014), great attention has been given to the separation of peaks that elute in very close retention times and are not clearly separated. Therefore, additional effort was put into the development of software that could clearly separate co-eluting peaks.…”
Section: Process Controller Hardware and Softwarementioning
confidence: 99%